2020
DOI: 10.1113/jp280247
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in subcellular muscle glycogen utilisation during exercise impacts endurance capacity in men

Abstract: When muscle biopsies first began to be used routinely in research on exercise physiology five decades ago, it soon become clear that the muscle content of glycogen is an important determinant of exercise performance. r Glycogen particles are stored in distinct pools within the muscles, but the role of each pool during exercise and how this is affected by diet is unknown. r Here, the effects of diet and exercise on these pools, as well as their relation to endurance during prolonged cycling were examined. r We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
76
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(84 citation statements)
references
References 69 publications
7
76
1
Order By: Relevance
“…We have previously found that a high glycogen utilization by type 1 fibres after 1 hour exhaustive cross‐country skiing (endurance exercise) was associated with a preferential utilization of intramyofibrillar glycogen, whereas a low utilization of glycogen by the type 2 fibres was associated with a preferential utilization of intermyofibrillar glycogen, altogether supporting the concept that intermyofibrillar glycogen is preferentially used during exercise with low levels of glycogen utilization 16 . On the other hand, 4‐minutes maximal ski sprinting resulted in only 22%‐24% reduced glycogen stores and if anything, intramyofibrillar and not intermyofibrillar glycogen deposits were preferentially used 17 and during endurance exercise a recent time‐course study found no preferential depletion of intermyofibrillar glycogen (or intramyofibrillar and subsarcolemmal glycogen) after 60 minutes of exercise compared with the depletion pattern of the different subcellular stores observed at exhaustion after around 112 minutes 18 . It remains to be understood how the continuous time‐course of glycogen depletion is characterized at the subcellular level, and how this is affected by the intensity and volume of exercise as well as the training state of the subject.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously found that a high glycogen utilization by type 1 fibres after 1 hour exhaustive cross‐country skiing (endurance exercise) was associated with a preferential utilization of intramyofibrillar glycogen, whereas a low utilization of glycogen by the type 2 fibres was associated with a preferential utilization of intermyofibrillar glycogen, altogether supporting the concept that intermyofibrillar glycogen is preferentially used during exercise with low levels of glycogen utilization 16 . On the other hand, 4‐minutes maximal ski sprinting resulted in only 22%‐24% reduced glycogen stores and if anything, intramyofibrillar and not intermyofibrillar glycogen deposits were preferentially used 17 and during endurance exercise a recent time‐course study found no preferential depletion of intermyofibrillar glycogen (or intramyofibrillar and subsarcolemmal glycogen) after 60 minutes of exercise compared with the depletion pattern of the different subcellular stores observed at exhaustion after around 112 minutes 18 . It remains to be understood how the continuous time‐course of glycogen depletion is characterized at the subcellular level, and how this is affected by the intensity and volume of exercise as well as the training state of the subject.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle glycogen was similarly depleted following all three sessions, demonstrating the importance of muscle glycogen availability and use to endurance exercise performance. The recent publication from Jensen et al (2020) in The Journal of Physiology took the original article by Bergström and colleagues (1967), in which they modified dietary content to manipulate muscle glycogen content prior to exhaustive exercise, and contemporarily upgraded it based upon novel analysis techniques. An identical study design was employed with some important additions ( Fig.…”
Section: Muscle Glycogen and Endurance Exercisementioning
confidence: 99%
“…In homage to the pioneers of skeletal muscle glycogen research, Jensen et al . (2020) followed the diet and exercise protocol of Bergström et al . (1967).…”
Section: Figure Intramyofibrillar Glycogen In Type I Fibres Best Predmentioning
confidence: 99%
“…Jensen et al . (2020) measured subcellular glycogen pools of vastus lateralis from subjects who consumed a mixed diet, a low carbohydrate diet, or a high carbohydrate diet and cycled at about 75% of V̇O2,max until exhaustion. The investigators biopsied vastus lateralis for glycogen measurement immediately before exercise, at exhaustion, and every hour for the mixed and high carbohydrate diets.…”
Section: Figure Intramyofibrillar Glycogen In Type I Fibres Best Predmentioning
confidence: 99%
See 1 more Smart Citation